Sex differences in the relationship between olfactory and cognitive impairment among subjects with subjective cognitive decline and mild cognitive impairment - Qin Liu; Ben Chen; Qiang Wang; Danyan Xu; Mingfeng Yang; Gaohong Lin; Yijie Zeng; Jingyi Lao; Shuang Liang; Jiafu Li; Kexin Yao; Xiaomei Zhong; et al. (Biology of Sex Differences)
Abstract Background Odor identification (OI) deficits are observed in both individuals with subjective cognitive decline (SCD) and mild cognitive impairment (MCI), and serve as risk factors for dementia. Compared with males, females typically demonstrate superior OI performance and different risks of dementia. However, the role of sex in the relationship between OI dysfunction and cognitive impairment remains uncertain. Methods In total, 121 subjects with SCD (41 males and 80 females), and 169 subjects with MCI (59 males and 110 females) underwent the Sniffin’ Sticks Screen 16 test and comprehensive neuropsychological examination. The relationships between olfactory and cognitive impairment were analyzed via partial correlation, multiple linear regression and moderating effects. Results In both SCD and MCI subjects, males performed better in language and females performed better in memory. The correlation between OI and cognition tended to be stronger in MCI subjects than in SCD subjects. In MCI subjects, the correlation tended to be stronger in females. For MCI females, better OI performance was correlated with higher short-term memory and attention scores. For MCI males, better OI performance was correlated with higher short-term memory scores. The OI was correlated with language in SCD males and with attention in SCD females. Sex played a moderating role in the relationship between OI dysfunction and language in MCI subjects and the relationship between OI dysfunction and short-term delayed recall memory and language in SCD subjects. Conclusion These findings revealed significant sex differences between OI dysfunction and cognitive impairment in SCD and MCI subjects. Sex differences should be considered when utilizing OI in clinical settings to predict cognitive function.